Developing supplier integration capabilities for sustainable competitive advantage: A dynamic capabilities approach - Vanpoucke, Evelyne; Vereecke, Ann; Wetzels, Martin (Journal of Operations Management, 2014)
AbstractPrevious research describes supplier integration as a competitive resource that manufacturers use to create economic rents. Considering the mixed results obtained from linking supplier integration with performance outcomes, a ‘dynamic’ component – or the ability to reconfigure the supply chain to adapt to changing environments – appears critical to creating a sustainable competitive advantage. This study identifies integration sensing, seizing and transforming as sub‐capabilities that together form a dynamic capability, referred to herein as supplier integrative capability (SIC). That is, SIC enables buyers to sense changes in the supply environment by sharing information with suppliers, seize opportunities presented by establishing procedures to analyse this information and make long‐term changes to existing processes. A global sample from the industrial sector reveals that the three capabilities exhibit complementarity and must exist simultaneously for the capability to be effective, which then enhances both process flexibility and cost efficiency and helps firms avoid the traditional trade‐off of cost and flexibility. In addition, market and technological dynamics strengthen the effect of SIC on operational performance; supply base complexity attenuates this link.